Extracellular Vesicles and Immunomodulation in Mosquitoes and Ticks - Brenda Leal-Galvan; Charluz Arocho Rosario; Adela Oliva Chávez (Encyclopedia, 2022)
Extracellular vesicles are small blebs that are secreted by cells, which are lipid-rich and contain proteomic and genomic material (including small RNAs, mRNA, and plasmid DNA). These materials are delivered into recipient cells leading to a phenotypic change. Recent studies have demonstrated the secretion of extracellular vesicles by mosquito and tick cells, as well as tick salivary glands. Further, these studies suggest vesicles play a role in the transmission of vector-borne pathogens, including viruses and bacteria, and are involved in the manipulation of wound healing and immune responses. Both of these processes are key in the host response to hematophagous arthropods’ feeding. The role of mosquito and tick EVs in the modulation of immune responses and pathogen transmission is discussed in this entry.